Research on Wireline Operators' Traffic-Based Operations Strategy - Ke Ruan; Ming Feng; Yongqing Zhu; Jie Zou (Dianxin kexue)
More and more telecom operators have been quick to embrace traffic-based operations. The industry and academia generally focus on the mobile internet, neglecting the wired markets. Aiming to explain the basic issues surrounding traffic-based operations on wired operators, the concept, characteristic and international operator's cases of the wired traffic-based operations were restudied. Finally, it was end with a series of conclusions and recommendations for wired traffic-based operations.